Multidisciplinary approach in the anterior open bite using a McNamara expander with palatal crib during mixed dentition stage: A case report - Wendes Dias Mendes; Paôla Caroline da Silva Mira; Paula Regina Ávila Silvan; Patrícia Maria Monteiro; Mirian Aiko Nakane Matsumot; Maria Bernadete Sasso Stuani (Arbu Academic Publishing, 2021)
Open bite can be defined as an absence of occlusion, most frequently located in the anterior region of dental arches and its etiology is multifactorial. We present a clinical case of an 8 years and 10 months child presenting an anterior open bite (AOB) with transverse maxillary deficiency caused by tongue thrust during mixed dentition. The malocclusion was corrected by means of a McNamara expander with a palatal crib jointly with the association of speech therapy for tongue repositioning, and otolaryngology to treat adenoid hypertrophy due to its correlation with AOB. The multidisciplinary approach was effective in correcting the malocclusion with stable results after 2 years post-treatment.